Técnica hidropónica y convencional en el rendimiento de Lactuca Sativa L. en Loreto - Aguirre Tapullima, Gilber Emanuel (2024)
This research evaluates the effect of cultivation techniques on the agronomic characteristics and yield of Lactuca sativa L. (lettuce) in the Loreto region, considering two systems: traditional horticultural beds and floating root hydroponics. The general objective was to determine the influence of both techniques on the agronomic characteristics and total yield of lettuce plants. A completely randomized design with two treatments and ten replications was used, evaluating variables such as height, width, leaf count, root length and weight, leaf weight, and total plant weight. Data were analyzed using ANOVA and Tukey's test (p < 0.01), employing coefficients of variation (CV) and adjusted determination coefficients (R²) to evaluate model precision and fit. The results revealed that the traditional horticultural bed technique was significantly superior in variables such as height (30.87 cm vs. 20.89 cm, p<0.01), width (30.30 cm vs. 23.42 cm, p<0.01), and total plant weight (151.06 g vs. 78.32 g, p<0.01). The hydroponic technique excelled in root length (11.70 cm vs. 5.87 cm, p<0.01) and root weight (9.94 g vs. 5.21 g, p<0.01),indicating its potential to optimize root development. It is concluded that the traditional horticultural bed technique is more suitable for maximizing total plant yield under local conditions, while hydroponics requires adjustments in nutrient management and temperature control to improve its efficiency. This research highlights the importance of techniques adapted to the climatic and edaphic context of Loreto, providing an approach to optimize sustainable horticultural production.